COMPARISON STUDY ABOUT DETERMINANTS OF CHILDREN UNDER FIVE YEARS MALNUTRITION BETWEEN INDIGENOUS AND NON-INDIGENOUS COMMUNITIES IN INDONESIA - Nurrizka, Rahmah Hida; Dwi Mutia Wenny; Agustina (Malaysian Journal of Public Health Medicine, 2020)
Many studies reveal the determinant factor of children under five years of malnutrition problem in Indonesia. However, there is only a few analysis conducted on indigenous communities and its comparison to non-indigenous communities. This study analyzes the determinant factors of malnutrition in children under five years in indigenous communities (Suku Baduy) and non-indigenous communities. This study is a comparative study using cross-sectional data, where the samples are households that have children under five years in indigenous communities (n=60) and in non-indigenous communities (n=60), with sample techniques using purposive random sampling. To calculate nutrition status, this study uses the anthropometric index based on weight-for-age according to WHO standards presented in the Z-score and Standard Deviations (SD). The result of this study indicates that the prevalence of children under five years suffering from malnutrition in indigenous communities is lower than in non-indigenous communities, which is 21,7% to 43,3%. Two factors influence the high prevalence of malnutrition in children under five years, namely, the education of the head of a family with OR=0.120 (95%C1: 0.021-0.675) and prenatal care in the fourth trimester with OR 9.890 (95%C1: 1.349-72.531). It is necessary to increase public knowledge on balanced nutrition in children under five years and improved maternal health access to resolve children under five years of malnutrition in those communities.